Management of Large Conjunctival Cysts in a Patient with Stevens-Johnson Syndrome: A Case Report and Review of the Literature - Sadid Hooshmandi; Kiana Hassanpour; Amirreza Veisi; Vahid Movafaghi; Farideh Langari; Mohammad-Mehdi Sadoughi; Mohammad Ali Javadi (Case Reports in Ophthalmology, 2023)
Stevens-Johnson syndrome (SJS) is a life-threatening mucocutaneous disease with various etiologies including drugs, infections, and malignancies. Ocular manifestations of SJS vary from the membrane, symblepharon formation, and epithelial defect in the acute phase to trichiasis, eyelid margin keratinization, and lacrimal duct obstruction in the chronic phase. A 13-year-old boy with a history of drug-induced SJS presented to our clinic complaining of a mass in the nasal side and inferior fornix of the right eye from 1 year ago. The mass-like lesion in the medial side of the right eye was accompanied by ankyloblepharon, symblepharon, and ptosis and limited ocular movement. Orbital imaging showed cystic lesions on the medial side of the right globe and the inferior fornix. Two large cysts were entirely surgically excised. Histopathologic investigation revealed conjunctival tissue with nonkeratinized epithelium and goblet cells. There was no sign of conjunctival cyst recurrence or symblepharon formation on the 6th-month follow-up. The inferior fornix achieved acceptable depth and the ocular movements became normal.